Review of Implementation of IMF Commitments in Support of the 2030 Agenda for Sustainable Development. (Policy Papers; Policy Paper ;, 2019)
The paper reviews the implementation of the initiatives the IMF committed to in 2015 to support developing countries in pursuing the 2030 agenda for sustainable development, including (i) strengthening national tax systems; (ii) tackling large infrastructure gaps; (iii) promoting economic inclusion; (iv) the development of domestic financial markets; (v) intensifying engagement in fragile and conflict-affected states; (vi) improving economic statistics; (vii) expanding the financial safety net for developing countries; and (viii) addressing macroeconomic aspects of climate change. The implementation record to date shows that there has been a large scaling up of IMF support for the 2030 development agenda. The IMF has also engaged in other initiatives of direct relevance for supporting the 2030 development agenda, including adopting a framework to assess corruption vulnerabilities and developing a broad framework for assessing the spending levels needed to reach key SDGs. The paper draws lessons learned from the implementation of the various initiative to inform future IMF engagements.